Quirks of the Quantum Mind by Robert G. Jahn and Brenda J. Dunne - Nelson, Sky Estabrook (Journal of Scientific Exploration, 2013)
<!-- gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]-->Quirks of the Quantum Mind accomplishes something that no other book to my knowledge has done. Using extensive data from the authors’ multiple decades of unique field research, Quirks synthesizes a “metaphor” which serves as a model for understanding consciousness-related anomalies. The book coherently presents a parallel between the principles of quantum mechanics and the psychic behavior observed in the research done at the Princeton Engineering Anomalies Research Laboratory. The authors do not presume to create a “theory” connecting quantum mechanics with consciousness. The authors steadfastly stick to the notion that quantum mechanics may serve as a metaphor for psychic phenomena. Yet they also make clear that the formalism of quantum mechanics itself is ultimately a reflection of the way we think. They point out that "common concepts of physical theories, such as mass, momentum and energy, electric charge and magnetic field, the quantum and the wave function, and even distance and time, are not more than useful organizing strategies consciousness has developed [for organizing its world]."<!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Calibri;} --> <!--[endif] -->